Optimizing Aceh’s Traditional Institutions to Provide Legal Protection for Children in Legal Conflict - Anggreini, Rini; Budi Bahreisy; Nurmalawaty (Acta Law Journal, 2024)
Children as the next generation of our nation, play a crucial role in the development and sustainability of a country. Society aspires to have children who are healthy, intelligent, cheerful, and assured of their survival and growth. However, the social reality often tells a different story, as many children must navigate the legal system for various reasons. Law Number 11 of 2012, concerning the Juvenile Criminal Justice System, introduces the concept of diversion. This concept aims to protect Children in Legal Conflict by shifting the resolution of their cases from the judicial process to an alternative process outside the criminal justice system. In this juvenile justice framework, Traditional Institutions also play an essential role. The involvement of community leaders in the implementation of the diversion agreement demonstrates that "traditional law" is still recognized and applicable in resolving children's cases. Based on this context, the study formulates the following questions: Why do Children in Legal conflicts have the right to protection? And how Optimizing Aceh’s Traditional Institutions can Provide Legal Protection for Children in Legal Conflict? The purpose of this study is to raise awareness and understanding of the significance of providing protection to Children in Legal Conflict while enhancing the role of Traditional Institutions in this legal protection. This research is categorized as normative legal research, utilizing secondary data obtained from legal materials. Data collection techniques include library research with qualitative data analysis. The findings reveal that children in legal conflict have the right to protection because Indonesia's ratification of the Convention on the Rights of the Child mandates it. This international commitment underscores key principles such as the best interests of the child, non-discrimination, survival and development, and respect for the child's participation, which must be prioritized in ensuring their protection. In this regard, the Aceh’s Traditional Institution plays a vital role in realizing this legal protection by resolving cases with an emphasis on deliberation. Therefore, optimizing the function of the Aceh’s Traditional Institution is necessary to achieve effective legal protection for children in conflict with the law.